East Asia and Pacific Update, April 2007 : Ten Years After the Crisis - World Bank (World Bank, Washington, DC, 2020)
Growth in Emerging East Asia accelerated to reach 8.1 percent in 2006. This was the strongest pace of economic expansion in the last ten years and a fitting commemoration of the decade that has passed since the start of the Asian financial crisis in 1997. The region's accomplishments in grappling with and overcoming the crisis and in returning to solid growth are varied and impressive -- a doubling in the dollar value of regional output from pre-crisis levels, the emergence of China into the front rank of global economic powers, a halving in poverty rates, accumulation of over 2 trillion dollars in foreign reserves. But even as the region celebrates recovery, new challenges are arising, which could slow or even derail growth if not properly handled. The report looks at these issues in a section on Ten years after the crisis. Another challenge of staggering proportions that lies ahead is East Asian urbanization: The region's population will rise by around 17 percent between 2000 and 2025 but its urban population will jump by 65 percent or 500 million. The Special Focus in this report on Sustainable Development in East Asia's Urban Fringe looks at the issues.